Islamization of Contemporary Knowledge: A Brief Comparison between Al-Attas and Fazlur Rahman - Wan Daud, Wan Mohd Nor (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Islamization of Contemporary Knowledge: A Brief Comparison between Al-Attas and Fazlur Rahman